(untitled) (Praxis Educativa, 2021)
This article presents the results of an ethnographic investigation carried out in a literacy workshop housed in a prison in the Province of Buenos Aires during 2017. In it, I seek to reconstruct the distance between the normative requirements referred to in the National Education Law 26.206/06 and in the National Law of Penal Enforcement 24.660/96 modified in August 2011 (through the enactment of Law 26.695/11) and the real possibilities of access to education. For this I will describe the way in which the processes of regulation of the school space were put into play from the prison management and how these practices were nuanced and strategically disputed in this educational space promoted and sustained by the imprisoned literacy teachers.